Genomic characterization and evolution analysis of peste des petits ruminants virus in China from 2007 to 2024 - Bao, Jingyue; Jiang, Ruiying; Wang, Shujuan; Wang, Qinghua; Xu, Jiao; Zhao, Yunling; Liu, Yutian; Li, Lin; Wang, Xiaohua; Wang, Zhiliang (Frontiers in Microbiology, 2025)
Peste des petits ruminants (PPR) is a highly contagious and lethal disease, primarily affecting sheep, goats, and wild small ruminants. Genomic characterization and evolutionary analysis of the circulating PPR virus (PPRV) strains can provide valuable information for the implementation of efficient control measures. In this study, we generated 28 novel PPRV full-length genome sequences from clinical samples collected during 28 PPR outbreaks in livestock and wildlife hosts across 15 provinces in China from 2014 to 2021. These genome sequences were compared with 135 published PPRV genome sequences, 37 of which were collected from China. The evolutionary rate of the PPRV genome was estimated to be 6.70 × 10−4 nucleotide substitutions per site per year. The predominant PPRV lineage IV can be divided into seven clades, demonstrating the temporal and spatial correlation. PPRV in China from 2007 to 2008 and 2013 to 2024 were grouped into two distinct genetic clades in lineage IV, indicating two independent incursions of the disease in 2007 and 2013. The PPRV in China from 2013 to 2024 shared a common ancestor with a strain from the UAE and evolved into four distinct genetic clusters, which did not exhibit distinct temporal, spatial, and host correlation. We used PPRV/XJYL/2013 as the reference genome, and 997 single-nucleotide variations (SNVs) were identified in PPRV genomes in China from 2013 to 2024. A total of five single-nucleotide variations, located in the 3′ leader, 5′ untranslated region (UTR) of the F gene, H cds, and L cds, were identified as anchor mutations, which defined the genetic clusters of PPRV during this period. One site in the H gene and five sites in the L gene were identified under positive selection. Our study provides significant insights into the molecular epidemiology, evolution, and transmission of PPRV, which will support the development of effective strategies for PPR control and eradication.